PENINGKATAN KETERAMPILAN MENULIS MAKALAH MELALUI METODE KOOPERATIF TIPE JIGSAW PADA MAHASISWA SEMESTER III STKIP YDB LUBUK ALUNG - Irawati Rahman (STKIP Pesisir Selatan, 2017)
Writing is one of the language capability which study since elementary until university. Based on observation and teach experience in student of STKIP YDB Lubuk Alung semester III, founded the fact that the student had dificult to write a paper and not understanding part of paper formation taht, so the student has not achieve of ability. It cause there have factor, such as using learning method. This classrom action research aim to describe and explain of capability witing paper on student of semester III STKIP YDB Lubuk Alung by using Cooperatif Learning Method Type Jigsaw. The populotion of the research was 27 Students in STKIPYDB Lubuk Alung. This research consist of two cycles with six lectures in july-December 2015-2016. Every cycles consist of : planning, action, observatio, reflection, and evaluation. The result of this research that the using cooperative Learning Method type Jigsaw can improve the ability writing paper and attention interesting student to learn part of paper formation in writing paper, specialy for students of STKIP YDB Lubuk Alung at july-December 2015-2016.